Analysis and modeling of complex data in behavioral and social sciences - Okada, Akinori; Ragozini, Giancarlo; Weihs, Claus; Vicari, Donatella (Studies in Classification, Data Analysis, and Knowledge Organization, 2014)
This volume presents theoretical developments, applications and computational methods for the analysis and modeling in behavioral and social sciences where data are usually complex to explore and investigate. The challenging proposals provide a connection between statistical methodology and the social domain with particular attention to computational issues in order to effectively address complicated data analysis problems. The papers in this volume stem from contributions initially presented at the joint international meeting JCS-CLADAG held in Anacapri (Italy) where the Japanese Classification Society and the Classification and Data Analysis Group of the Italian Statistical Society had a stimulating scientific discussion and exchange.